2014
DOI: 10.1007/s00296-014-3188-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on early arthritis: a cross-sectional study—data from the Argentine Consortium for Early Arthritis (CONAART)

Abstract: Our objective was to analyze the effects of cigarette smoking on disease activity, functional capacity, radiographic damage, serology and presence of extraarticular manifestations in patients with rheumatoid arthritis and undifferentiated arthritis. This is a cross-sectional study of 1,305 patients (729 with rheumatoid arthritis and 576 with undifferentiated arthritis) from CONAART, the Argentine Consortium for Early Arthritis that includes patients older than 16 years with <2 years of disease. Sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The association of smoking with development and severity of RA was documented almost 30 years ago [10] and confirmed in many subsequent studies [11][12][13][14][15][16][17][18][19][20][21]. A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19].…”
Section: Smoking and Ramentioning
confidence: 76%
“…The association of smoking with development and severity of RA was documented almost 30 years ago [10] and confirmed in many subsequent studies [11][12][13][14][15][16][17][18][19][20][21]. A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19].…”
Section: Smoking and Ramentioning
confidence: 76%
“…Finally, in the assessment of multiple variables, type 1 statistical error may arise from chance such as the association of smoking with arthropathy. However, with the variable of arthritis, biological plausibility of smoking affecting joints is present in current smokers with rheumatoid/undifferentiated arthritis having increased joint disease activity and radiological joint erosions . Strengths of this study include its large number of patients, inclusion of both CD and UC patients, the extended follow‐up period and the width of clinical outcomes interrogated; ensuring comprehensive characterisation of disease course in smokers, ex‐smokers and never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the variable of arthritis, biological plausibility of smoking affecting joints is present in current smokers with rheumatoid/undifferentiated arthritis having increased joint disease activity and radiological joint erosions. 59 Strengths of this study include its large number of patients, inclusion of both CD and UC patients, the extended follow-up period and the width of clinical outcomes interrogated; ensuring comprehensive characterisation of disease course in smokers, ex-smokers and never smokers. Translatable outcomes from this study include the association between arthritis and smoking in CD suggesting another possible avenue for treating this disabling extra-intestinal manifestation, and the lack of benefit of ongoing smoking on the natural history of UC, recommending cessation of smoking be offered to all patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…CONAART also informed about work disability and its main associated factors in patients with ERA [ 43 ]. They also analyzed the effects of cigarette smoking on disease activity, functional capacity, radiographic damage, serology, and presence of extra-articular manifestations in patients not only with ERA, but also with undifferentiated arthritis, and found that neither was tobacco exposure related to the presence of extra-articular manifestations or to the degree of disability in any of the two groups of patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%